Panic attack provocation in panic disorder patients with a computer simulation - Freire, Rafael Christophe; Ferreira-Garcia, Rafael; Cabo, Mariana Costa; Martins, Renan Machado; Nardi, Antonio Egidio (Journal of affective disorders, 2020)
•Forty percent of the PDA patients had panic attacks after exposure to the CS.•Patients also had higher SUDS and DSQ scores than the healthy controls.•The sense of presence was indistinguishable between the patients and controls.•The CS produced hyperventilation in PDA patients, but not in healthy subjects.•The CS induced highest SCL increases in PDA patients who had panic attacks. Computer simulations (CS) and virtual reality exposure are promising techniques for research and treatment of panic disorder with agoraphobia (PDA). The objective of this study was to ascertain whether a given CS was a stimulus capable of producing panic attacks (PAs), anxiety and psychophysiological changes in patients with PDA. Thirty PDA patients and 30 healthy subjects were recruited for this study. Subjects were exposed to a 3-min CS of a situation relevant to agoraphobic patients. Anxiety, panic symptoms, PAs, heart rate, skin conductance and respiration were recorded before, during and after the CS exposure. The CS effectively induced anxiety, hyperventilation and electrodermal responses in PDA patients but not in healthy subjects. Forty percent of PDA patients had a PA while none of the control subjects had a PA. A subgroup of patients who were less sensitive to the CS than the other subgroup of PDA patients and did not present full-blown PAs still had more panic symptoms, higher anxiety levels and more respiratory irregularities than the controls. Low immersion and low sense of presence, lack of interaction with the environment. Exposure to the CS produced effects similar to in vivo exposure, respiratory and caffeine challenges. Subsequent studies should: make direct comparisons between CS and other challenges for PDA; investigate if CS can be a tool for predicting effects of medication; determine the potential of CS as a desensitization technique for situational PAs.